PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN (Studi Kasus PT. Capella Dinamik Nusantara Cab. Kandis) - Purba, Berto Kristanto; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of Compensation and Working Environment Employee Loyalty (Case Study PT. Capella Dinamik Nusantara Cab. Kandis). Compensation as a variable (X1), Environmental Working as a variable (X2) and employee loyalty as a variable (Y).The method in this research is descriptive and quantitative with program SPSS, where samples were used that all employees as many as 25 respondents. To determine the sample, this study used census techniques. Data collection through questionnaires.The study concluded that the variable compensation positive effect on employee loyalty, work environment positive effect on employee loyalty and significant influence between compensation and work environment on employee loyalty.Keywords: Compensation, environment work and employee loyalty